Postoperative hemorrhage after biomedical glue sling technique in microvascular decompression for vertebrobasilar artery-associated cranial nerve diseases: A retrospective study of 14 cases - Liu, Jiang; Shen, Yuxiao; Xiayizhati, Kelisitan; Yu, Yanbing (Frontiers in Surgery, 2023)
Background: Biomedical glue sling technique is a convenient and effective method for vertebrobasliar artery associated cranial nerve diseases but postoperative hemorrhage is poorly understood. Methods: We retrospectively reviewed 14 of 1157 patients associated with cranial nerve diseases who underwent biomedical glue sling technique in microvascular decompression in our hospital from January 2015 to January 2020. Results: There were 14 patients with cranial nerve diseases included in this study. The average time was 41.75 hours (range 0.5h-95h), which the onset of postoperative hemorrhage was diagnosed clinically. Five patients developed cerebellopontine angle hemorrhage and basal ganglia hemorrhage were observed in two patients. One patient developed both cerebellopontine angle and brainstem hemorrhage. Six patients developed distant supratentorial subdural hemorrhage. The correlation coefficient was -0.1601 (p=0.7094) between standard deviation of systolic blood pressure and Hempill Score, -0.2422 (p=0.5633) between coefficient of variation of systolic blood pressure and Hempill Score, -0.0272 (p=0.9489) between range of systolic blood presssure and Hempill Score. Conclusions: The incidence of postoperative hemorrhage after MVD with biomedical glue sling technique higher than traditional MVD and most cases have favorable prognosis. Postoperative symptoms are the main areas of concern and changes in symptoms usually suggest occurrence of hemorhage. Several factors, including surgical procedures, releasement of CSF and blood pressure might be associated with hemorrhage. We still believe such technique is a safe and efficient approach to treat complicated cranial nerve diseases.